An Approach to Establishing International Quality Standards for Medical Travel - Kácha, Ondřej; Kovács, Beáta E.; McCarthy, Cormac; Schuurmans, Angela A. T.; Dobyns, Christopher; Haller, Elisa; Hinrichs, Saba; Ruggeri, Kai (Frontiers in Public Health, 2016)
Traveling abroad to receive a non-elective treatment is expanding each year. Such rising popularity of medical travel and the absence of clear minimum quality requirements in this area urgently calls for setting international standards to ensure good practice and patient safety. The aim of this study is to identify the key domains in medical travel where such quality standards should be established. Drawing from the evidence-based OECD framework and an extensive literature review, this study proposes three critical areas for international quality standards in medical travel: minimum standards of health care facilities and third-party agencies, financial responsibility and patient-centeredness. Several cultural challenges are subsequently introduced that may pose a barrier to the development of the guidelines and should be additionally taken into consideration. Establishing international quality standards in medical travel enhances the benefits to patients and providers, which is urgently needed given the rapid growth in this industry.